Pengaruh Persepsi Manfaat, Persepsi Kemudahan dan Persepsi Resiko Terhadap Keputusan Penggunaan Go-Pay - Waheni, Ni Komang; Hartati, Putu Sri; Purwaningrat, Putu Atim (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This research was conducted with the aim of looking at the effect of perceived benefits, perceived convenience, and perceived risk on the decision to use Go-pay among students at the Hindu University of Indonesia. The sample used in this study was 97 students, out of 3175 students at the Hindu University of Indonesia determined by purposive sampling method. The data analysis techniques used in this study were validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test and F test. Based on the results of the study, it can be seen that: Perceived benefits, perceived convenience, and perceived risk have a positive and significant effect partially and simultaneously on the decision to use Go-pay. The magnitude of the influence of the independent variable on the decision to use Go-pay is 99.2%. The suggestion that Go-Jek hopes is to increase its usefulness for consumers by improving the quality of application features, and lowering administrative costs for consumers who want to use it.